Once induced, it lasts for a long time: the structural and molecular signatures associated with depressive-like behavior after neonatal immune activation - Khantakova, Julia N.; Bondar, Natalia P.; Antontseva, Elena V.; Reshetnikov, Vasiliy V. (Frontiers in Cellular Neuroscience, 2022)
Adverse factors such as stress or inflammation in the neonatal period can affect the development of certain brain structures and have negative delayed effects throughout the lifespan of an individual, by reducing cognitive abilities and increasing the risk of psychopathologies. One possible reason for these delayed effects is the neuroinflammation caused by neonatal immune activation (NIA). Neuroinflammation can lead to disturbances of neurotransmission and to reprogramming of astroglial and microglial brain cells; when combined, the two problems can cause changes in the cytoarchitecture of individual regions of the brain. In addition, neuroinflammation may affect the hypothalamic–pituitary–adrenal (HPA) axis and processes of oxidative stress, thereby resulting in higher stress reactivity. In our review, we tried to answer the questions whether depressive-like behavior develops after NIA in rodents and what the molecular mechanisms associated with these disorders are. Most studies indicate that NIA does not induce depressive-like behavior in a steady state. Nonetheless, adult males (but not females or adolescents of both sexes) with experience of NIA exhibit marked depressive-like behavior when exposed to aversive conditions. Analyses of molecular changes have shown that NIA leads to an increase in the amount of activated microglia and astroglia in the frontal cortex and hippocampus, an increase in oxidative-stress parameters, a change in stress reactivity of the HPA axis, and an imbalance of cytokines in various regions of the brain, but not in blood plasma, thus confirming the local nature of the inflammation. Therefore, NIA causes depressive-like behavior in adult males under aversive testing conditions, which are accompanied by local inflammation and have sex- and age-specific effects.